Masalah Perilaku pada Anak Sindroma Nefrotik - Barus, Ratna Sari; Ramayani, Oke Rina; Siregar,, Rosmayanti; Siregar, Beatrix (Majalah Kedokteran Nusantara The Journal Of Medical School, 2017)
Nephrotic syndrome (NS) is the most common chronic kidney disease in children.As one of chronic diseases having remission and relapse periods and requiring longterm corticosteroid theraphy, NS has impacts on childrenâs biologic, social, and behavior functions which will affect psychosocial developmen of the children and their families. Untill now there were difficulties in determining behavioural problem in children with NS and to determine whether it was caused by the disease itself or by chronic condition or by the side effect of steroid theraphy. High-dose steroid usage, mainly in the early treatment phase of NS is proven to correlate with internalization behavioural problem, manifesting with anxiety, depression, aggressiveness, and retraction from social life.It is suggested to pay more attention to psychosocial problems in children with NS especially in the early phase of steroid theraphy.Keywords : nephritic syndrome, children, behavioral problem, steroidTinjauan Pustaka